Investigation of the effectiveness of use of youtube as a learning resource - La Djuma (Balai Diklat Keagamaan Ambon, 2023)
This article was prepared with the aim of investigating the effectiveness of using YouTube as a learning resource in training activities. The method used in this article is a literature study related to YouTube, learning media, and interest in learning and training. The results of the study found that the use of YouTube as a source of learning in training activities showed a positive trend towards the knowledge and interest in learning of the trainees. Therefore, YouTube can be used as an alternative a learning resource for trainees.